Monitoring of a Laboratory‐Scale Inland‐Delta Formation using a Structured‐Light System. (June 2016) - Akca, Devrim; Seybold, Hansjörg
Abstract: A reduced complexity model, which simulates the process of fluvial inland‐delta formation, has been developed in a previous study. The results have been compared and validated with a laboratory experiment. This work elaborates the laboratory investigation in which an experimental inland delta is generated and its eroding topography is measured using a structured‐light 3D scanner. The least squares 3D (LS3D) co‐registration and comparison method is used for alignment as well as for comparing data epochs both spatially and temporally. A spatial precision value of around ±50 μm (1/20 000) is achieved. A series of high‐quality digital elevation models (DEMs) are generated and the space‐time evolution of the inland delta is monitored and analysed, in terms of slope and topography dynamics, in the consecutive DEM layers. The combination of high‐resolution scanning together with high‐precision co‐registration techniques allows investigation of the details of the space‐time variability of the sedimentation‐deposition patterns to be used for geomorphological analysis.